Strategies used in the writing process by ESL students through the implementation of project-based learning (PjBL) in evaluative writing. - Rosli, Nurul Farihah; Abdul Rahman, Nurul Ajleaa; Goh, Y. S.,,; Azman, Nur Nabila; Chen, C., (Journal of Islamic, Social, Economics and Development, 2026)
This study explores the strategies employed by English as a Second Language (ESL) students during the writing process in a Project-Based Learning (PjBL) environment. Writing in English presents significant challenges for ESL students, necessitating the use of specific strategies to enhance their writing skills. Unlike general writing tasks, evaluative writing requires students to critically assess sources, synthesize information, and present well-structured arguments, posing unique challenges. The study focuses on students from three different performance levels—high, moderate, and low—providing a nuanced understanding of how learners with varying proficiencies approach writing in a PjBL setting. This study adopts a qualitative case study approach, analyzing semi-structured interviews conducted with nine ESL students across three classes over a nine-week period. The findings indicate that students used various strategies during the prewriting, drafting, revising, and editing stages. These strategies include brainstorming, outlining, utilizing dictionaries and technological tools, translating from their native language, and employing synonyms to refine their writing. Notably, high-performing students demonstrated greater autonomy in structuring arguments, while low-performing students relied more on external resources and peer support. These insights contribute to the growing body of research on PjBL and highlight its potential in fostering evaluative writing skills among ESL learners.